Answer:
a) x =3 and x=5
c) x =-1 and ![x = \frac{-7}{3}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B-7%7D%7B3%7D)
i) x =0 and ![x = \frac{-9}{2}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B-9%7D%7B2%7D)
Step-by-step explanation:
a)
Given that the quadratic equation
x² - 8x +15 =0
The factors of 15 = 5 × 3
x² - 5x -3x +15 =0
x(x -5) -3(x-5) =0
(x-3)(x-5) =0
x =3 and x=5
c)
3 x² + 10 x +7 =0
⇒ 3x² + 3x + 7x +7 =0
⇒ 3x (x +1) +7(x+1) =0
⇒ (x+1) ( 3 x +7) =0
⇒ x =-1 and ![x = \frac{-7}{3}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B-7%7D%7B3%7D)
i)
2 x ² + 9 x =0
⇒ x( 2 x + 9) =0
⇒ x =0 and 2 x = -9
⇒ x =0 and ![x = \frac{-9}{2}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B-9%7D%7B2%7D)
I uploaded the answer to a file hosting. Here's link:
bit.
ly/3a8Nt8n
1250/10=125
Hope this helps and have and AWESOME night!!! :)
Answer:
One: x = 3/32
Two: y = 3/10
Step-by-step explanation:
One
y = k*x
1/4 = k* 1/8 Multiply both sides by 8
8(1/4) = 8*k*(1/8)
8/4 = k
k = 2
=======================
3/16 = 2*x Divide by 2
3/32 = x
Two
y = 2/5
x = 1/3
2/5 = k * 1/3 Multiply both sides by 5
2 = 5*k * 1/3
2 = 5/3 * k Multiply both sides by 3
6 = 5 * k Divide both sides by 5
6/5 = k
y = 6/5 * x
x = 1/4
y = 6/5 * 1/4
y = 6/20 = 3/10